Building Background Knowledge through Reading: Rethinking Text Sets - Lupo, Sarah M; Strong, John Z; Lewis, William; Walpole, Sharon; McKenna, Michael C (Journal of adolescent & adult literacy, 2018)
To increase reading volume and help students access challenging texts, the authors propose a four-dimensional framework for text sets. The quad text set framework is designed around a target text: a challenging content area text, such as a canonical literary work, research article, or historical primary source document. The three remaining dimensions include visual texts (e.g., a video, pictures), informational texts to build students' background knowledge and vocabulary, and an accessible young adult novel or current events article to help students engage with the topic. Working together, these texts can build students' background knowledge, make the target text accessible to students, and also allow them to synthesize information across sources. The authors suggest that quad text sets are useful in English, science, and social studies classrooms.